Activating Mud Beach Performing Art Attraction and Art Gallery for Community-Based Tourist Destination at Bandar Rahmat Village of Tanjung Tiram District, Batubara Regency - Hutajulu, Rithaony; Arifninetrirosa; Sujatmoko, Koko (Talenta Publisher, 2023)
This Community Partnership Service program aims to activate the mud beach art attractions and art galleries for community-based tourism management in Bandar Rahmat, Tanjung Tiram District, Batubara Regency. This activation program will increase partners' awareness and skills for managing community-based tourist destination. The specific target of this activity is for partners to produce an art attraction based on local conditions as long-term management of tourist destinations through the art galleries. Partners can turn existing conditions into a potential for increasing tourism-economic income. The method used in achieving this activation is problem-facing assistance. The team will conduct training on the cultivation of works of art based on local conditions as well as training on art gallery management. This training will involve youth in partner villages. The indicator of the success of this program is that the partners can produce artistic attractions and establish a legal entity art studio. These two things will be the key to the sustainability of the long-term development of tourist destinations and increasing tourism-economic income in partner villages.